1994
DOI: 10.4315/0362-028x-57.4.324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trisodium Phosphate on Campylobacter Attached to Post-Chill Chicken Carcasses

Abstract: Trisodium phosphate (TSP) was evaluated as a means to reduce Campylobacter on chicken carcasses. Post-chill chicken carcasses were dipped into a 10% TSP solution at 50°C for 15 s. After storing the TSP-treated carcasses for 0, 1 or 6 days at 4°C, the carcasses were subjected to the recovery of Campylobacter. The incidence and reduction of Campylobacter attached to the carcasses were measured using a nitrocellulose (NC) membrane lift, conventional culture method, and a most probable number (MPN) technique. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 0 publications
1
22
0
5
Order By: Relevance
“…Log reductions in viable counts of 1.4 and 0.9 were obtained for Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium, respectively, on beef adipose tissue, although significantly lower reductions (0.9 and 0.5, respectively) were observed on fascia (19). On chicken carcasses, Slavik et al (34) and Kim et al (20) showed that TSP treatment at 10 or 50°C reduced Salmonella counts by 1.6 to 1.8 log units per carcass, and in a scanning electron microscopic study Kim and Slavik (18) showed TSP effectively removed attached Salmonella organisms from chicken skin.…”
mentioning
confidence: 96%
“…Log reductions in viable counts of 1.4 and 0.9 were obtained for Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium, respectively, on beef adipose tissue, although significantly lower reductions (0.9 and 0.5, respectively) were observed on fascia (19). On chicken carcasses, Slavik et al (34) and Kim et al (20) showed that TSP treatment at 10 or 50°C reduced Salmonella counts by 1.6 to 1.8 log units per carcass, and in a scanning electron microscopic study Kim and Slavik (18) showed TSP effectively removed attached Salmonella organisms from chicken skin.…”
mentioning
confidence: 96%
“…Spraying carcasses with different salt solutions and antibacterial agents, such as trisodium phosphate, has been investigated (23). However, this presents problems of acceptability and possible deterioration of the organoleptic properties of the chicken (e.g., taste, texture, and odor).…”
mentioning
confidence: 99%
“…TSP is naturally present in tissues and bones and may thus be considered to be harmless (Skovgaard 1996) and, under authorized conditions, does not affect the sensory quality of the product (Giese 1993;Hollender et al 1993;Coppen 1994;Hathcox et al 1995;Ellerbroek et al 1997;Capita et al 2000a). The antimicrobial activities of TSP against Salmonella, Escherichia coli, Campylobacter, Pseudomonads, spoilage microbes and Staphylococcus aureus are well documented (Bender and Brotsky 1992;Dickson et al 1994;Lee et al 1994;Lillard 1994;Salvat et al 1994;Slavik et al 1994;Somers et al 1994;Federighi et al 1995;Fratamico et al 1996;Rodrõ Âguez de Ledesma et al 1996;Capita et al 2000b). However, there is little published research on the effectiveness of TSP against L. monocytogenes.…”
Section: Introductionmentioning
confidence: 99%